Epistemology - Fumerton, Richard A., 1949- (Malden, MA : Blackwell Pub., 2006)
"Epistemology is an accessible introduction to a topic of fundamental importance in philosophy. This distinctive book first highlights some of the serious questions about belief and knowledge that arise in real-life situations, then demonstrates the manner in which these questions naturally lead to deeper concerns about evidence, justification, and theories of knowledge." "Combining intriguing examples with careful argument and analysis, Epistemology provides a comprehensive and through-provoking overview appropriate for anyone new to philosophy."--Jacket
The analysis of knowledge -- Epistemic rationality and its structure -- Traditional (internalist) foundationalism -- Externalist versions of foundationalism -- Inferential justification -- Metaepistemology and skepticism
Includes bibliographical references (pages 137-139) and index
Keywords: Knowledge, Theory of; Lehrbuch